Bridging the Last Mile for Optical Switching in Data Centers - Ballani, Hitesh; Costa, Paolo; Haller, Istvan; Jozwik, Krzysztof; Shi, Kai; Thomsen, Benn; Williams, Hugh (Optical Fiber Communication Conference (OFC), 2018)
Optical switches promise to revolutionize data centers by providing high bandwidth and low latency at low cost. This paper discusses some of the remaining challenges that need to be solved to make this technology successfully deployed in production.